2022
DOI: 10.5037/jomr.2022.13102
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin/Metronidazole Dose Impact as an Adjunctive Therapy for stage II - III grade C Periodontitis (Aggressive Periodontitis) at 3- And 6-Month Follow-Ups: a Systematic Review and Meta-Analysis

Abstract: Objectives: This systematic review and meta-analysis study sought to review the efficacy of amoxicillin/metronidazole dose and duration time in the treatment of stage II -III grade C periodontitis (aggressive periodontitis) after current follow-up. Material and Methods: An electronic search of the literature was performed in three main databases for relevant articles published until 31 th of December 2021. According to the PRISMA statement, the extracted data from selected articles were pooled. The weighted me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 69 publications
1
7
0
2
Order By: Relevance
“…Finding of this research is somehow similar found in previous study, done in Dental College and Research Institute, of India where metronidazole gel, and chlorhexidine gel were used in periodontal problems (20) , another trial was also taken as a reference for this research which demonstrated the effectiveness of usage of metronidazole gel, on overgrowth of gingiva due to cyclosporine (21) However, this study shows clinically and statically significant reductions of periodontal inflammation in all three treatment groups from baseline to 12 th week.…”
Section: Discussionsupporting
confidence: 88%
“…Finding of this research is somehow similar found in previous study, done in Dental College and Research Institute, of India where metronidazole gel, and chlorhexidine gel were used in periodontal problems (20) , another trial was also taken as a reference for this research which demonstrated the effectiveness of usage of metronidazole gel, on overgrowth of gingiva due to cyclosporine (21) However, this study shows clinically and statically significant reductions of periodontal inflammation in all three treatment groups from baseline to 12 th week.…”
Section: Discussionsupporting
confidence: 88%
“…In this case, the combination of amoxicillin-metronidazole has the 21st rank among the 25 most frequently selected variables, which has the highest importance in making an accurate prediction. This is despite the fact that the recent systematic review and meta-analysis research about simultaneously amoxicillin/metronidazole usage in periodontitis treatment has shown positive shortterm effects [26]. In addition, considering the extracted results showed that acetaminophen existed in several 2combs.…”
Section: Discussionmentioning
confidence: 90%
“…The systemic administration of antibiotics to patients with chronic periodontitis has been mainly employed as an adjunct to scaling and root planning, and the best clinical results are obtained with the combination of amoxicillin and metronidazole [ 4 ]. This combination of antibiotics is especially effective in terms of clinical attachment level gain and probing depth reduction in patients with aggressive periodontitis [ 5 , 32 ]. The systemic disorders that have a major impact on the loss of periodontal tissues by influencing periodontal inflammation include neutropenia [ 8 ].…”
Section: Discussionmentioning
confidence: 99%